2021
DOI: 10.1038/s41598-021-92247-3
|View full text |Cite
|
Sign up to set email alerts
|

Electro-steric opening of the clc-2 chloride channel gate

Abstract: The widely expressed two-pore homodimeric inward rectifier CLC-2 chloride channel regulates transepithelial chloride transport, extracellular chloride homeostasis, and neuronal excitability. Each pore is independently gated at hyperpolarized voltages by a conserved pore glutamate. Presumably, exiting chloride ions push glutamate outwardly while external protonation stabilizes it. To understand the mechanism of mouse CLC-2 opening we used homology modelling-guided structure–function analysis. Structural modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In contrast, the protopore gates are located in each protomer. Similar to other ClC proteins, three residues were identified in ClC-2 in the potential chloride binding sites along the channel (S162, E205 and Y553 in human ClC-2; S168, E211 and Y559 in rat ClC-2; S170, E213 and Y561 in mouse ClC-2) 18 , 41 , 42 . Structural modeling and electrophysiological recording experiments demonstrated that E213 and Y561 in mouse ClC-2 are energetically coupled in the closed state 41 .…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In contrast, the protopore gates are located in each protomer. Similar to other ClC proteins, three residues were identified in ClC-2 in the potential chloride binding sites along the channel (S162, E205 and Y553 in human ClC-2; S168, E211 and Y559 in rat ClC-2; S170, E213 and Y561 in mouse ClC-2) 18 , 41 , 42 . Structural modeling and electrophysiological recording experiments demonstrated that E213 and Y561 in mouse ClC-2 are energetically coupled in the closed state 41 .…”
Section: Introductionmentioning
confidence: 63%
“…Similar to other ClC proteins, three residues were identified in ClC-2 in the potential chloride binding sites along the channel (S162, E205 and Y553 in human ClC-2; S168, E211 and Y559 in rat ClC-2; S170, E213 and Y561 in mouse ClC-2) 18 , 41 , 42 . Structural modeling and electrophysiological recording experiments demonstrated that E213 and Y561 in mouse ClC-2 are energetically coupled in the closed state 41 . Upon occupied by Cl − ion, the Y561-E213 coupling is disrupted by electrostatic and steric repulsion, E213 is then repelled outward to adopt an outward-facing conformation 41 .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, in voltage-gated Cl − channels CLC-0 and CLC-1, a Cl − ion could be responsible for opening a glutamate gate protruding the permeation pathway ( Pusch et al, 1995 ; Chen and Miller, 1996 ; Chen, 2003 ; Pusch, 1996 ; Rychkov et al, 2001 ). Furthermore, we showed that the interaction between the hyperpolarization-propelled intracellular Cl − and the pore gate triggers CLC-2 gating ( De Jesús-Pérez et al, 2016 , 2021 ; Sánchez-Rodríguez et al, 2010 , 2012 ). In TMEM16B, highly permeable anions facilitated the voltage-gated opening and increased the apparent Ca 2+ sensitivity ( Betto et al, 2014 ).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, there are substantial differences between CLC-2’s “slow” gating mode and CLC-0’s common gating in terms of kinetics and temperature dependence. Moreover, unlike CLC-0 (Lin et al, 1999), CLC-2 slow and fast gating cannot be separately affected by mutation (Zuniga et al, 2004; de Santiago et al, 2005; Yusef et al, 2006; De Jesus-Perez et al, 2021). Finally, in contrast to CLC-0, it has not been demonstrated that the “slow” gate in CLC-2 corresponds to a common gating process operating on both pores simultaneously.…”
Section: Discussionmentioning
confidence: 99%